2019
DOI: 10.1002/jcp.29180
|View full text |Cite
|
Sign up to set email alerts
|

Targeting epigenetic modifications as a potential therapeutic option for diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is the leading cause of visual impairment in adults of working age (20-65 years) in developed countries. The metabolic memory phenomena (persistent effect of a glycemic insult even after retrieved) associated with it has increased the risk of developing the complication even after the termination of the glycemic insult. Hence, the need for finding early diagnosis and treatment options has been of great concern. Epigenetic modifications which generally occur during the beginning stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 168 publications
1
21
0
Order By: Relevance
“…Diabetes is a serious and complex disease characterized by chronic hyperglycemia, which aggravates a series of metabolic reactions and increases the production of advanced glycosylation end products (aGes). it has been reported that in diabetes the development of AGE-induced retinal inflammation results in blood-retinal barrier damage, which in turn leads to diabetic macular edema and retinal neovascularization (1,2). Although blood glucose control has been reported to significantly reduce the incidence of microvascular complications, some patients still suffer from proliferative diabetic retinopathy (dr) for >30 years (3).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a serious and complex disease characterized by chronic hyperglycemia, which aggravates a series of metabolic reactions and increases the production of advanced glycosylation end products (aGes). it has been reported that in diabetes the development of AGE-induced retinal inflammation results in blood-retinal barrier damage, which in turn leads to diabetic macular edema and retinal neovascularization (1,2). Although blood glucose control has been reported to significantly reduce the incidence of microvascular complications, some patients still suffer from proliferative diabetic retinopathy (dr) for >30 years (3).…”
Section: Introductionmentioning
confidence: 99%
“…The level of MMP-9 differs with the stages of DR and was found to contribute more than MMP-1 in DR pathogenesis (Kwon et al, 2016). Various histone modifications, DNA methylations, and their role in metabolic memory formation (Mishra and Kowluru, 2016;Kumari et al, 2020) are reported for MMP9 during hyperglycemic conditions. SPARC (Secreted Protein Acidic And Cysteine Rich), a gene that encodes cysteine-rich acidic matrix-associated protein, is also involved in the development of DR. Retinal basement membrane of Type2DM patients showing thickening and permeability changes is found to secrete the protein encoded by SPARC (Watanabe et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Various epigenetic modifications such as DNA methylation, histone modifications, microRNA (miRNA), etc., occurring during the early stage of diabetes do not only regulate the expression of various genes but are also responsible for the metabolic memory phenomena (deleterious effect induced by prior glycemic exposure regardless of later glycemic control) associated with diabetes (Mishra and Kowluru, 2016;Kumari et al, 2020). This triggers the need for developing early diagnosis and treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic modifications regulate the complex interplay between genes and environmental factors without altering the DNA sequence (Kowluru & Mishra 2015; Kumari et al 2019). The three major classes of epigenetic factors are DNA methylation, histone modification and non‐coding RNAs (ncRNAs) (Kowluru & Mishra 2015; Kumari et al 2019). NcRNAs are regulatory RNAs that lack protein‐coding capacity.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the most widely studied class of ncRNAs are miRNAs, which are small ncRNAs of ~22 nt that regulate expression of more than 60% of protein‐coding genes, consequently controlling various biological and pathological processes, such as cellular growth, apoptosis, differentiation, metabolism and immune response (Esteller 2011; Assmann et al 2017b; Martinez & Peplow 2019; Satari et al 2019). Growing evidence suggests the involvement of several miRNAs in DR pathogenesis (Joglekar et al 2016; Gong & Su 2017; Kumari et al 2019; Martinez & Peplow 2019; Satari et al 2019). MiRNA‐126 expression seems to be downregulated in serum of diabetic patients with DR (Rezk et al 2016; Barutta et al 2017; Qin et al 2017; Martinez & Peplow 2019), endothelial cells (ECs) and retinal pericytes of a murine DR model (Fang et al 2017), and in retina of streptozotocin (STZ)‐induced diabetic rats (Ye et al 2014).…”
Section: Introductionmentioning
confidence: 99%